Giftedness and Overexcitability: Investigating the Relationship Using Meta-Analysis. (October 2016) - Winkler, Daniel; Voight, Adam
Current textbooks, websites, research articles, and popular resources have stated that gifted individuals have longer and more pronounced responses to stimuli than the general population. This overexcitable nature of gifted persons has provided a commonly used lens to conceptualize, identify, and understand giftedness and gifted persons' behaviors. Yet there are reasons to be skeptical about the evidence demonstrating that the gifted population is more overexcitable than the nongifted population. A meta-analysis was conducted to investigate the existence and strength of the giftedness–overexcitability (OE) relationship as presented in a number of studies comparing the OE scores of intellectually gifted and nongifted samples. Gifted samples were found to have higher mean OE scores than nongifted samples. However, the effect size for psychomotor OE was not statistically significant, while the effect sizes for the emotional and sensual OEs were small. Calculated effect sizes for intellectual and imaginational OEs were medium. A number of important limitations and implications exist.